Efficacy of Mindfulness-Based Interventions for Attention and Executive Function in Children and Adolescents—a Systematic Review - Mak, C.; Whittingham, K.; Cunnington, R.; Boyd, Roslyn (Springer New York LLC, 2018)
The purpose of this study was to evaluate the efficacy of mindfulness-based interventions including mindful movements such as yoga on attention and executive function in children and adolescents. Systematic searches were conducted on five databases (PubMed, PsycINFO, CINAHL, Web of Science, and Scopus). Included studies consisting of randomized or quasi-randomized controlled trials with a mindfulness-based intervention were assessed for quality, and relevant data was extracted and collated. Thirteen randomized control trials were identified as meeting inclusion criteria, including mindfulness-based psychological interventions (n = 7), yoga (n = 3), and traditional meditation techniques (n = 2). Studies recruited adolescents or children that were typically developing, diagnosed with attention-deficit hyperactivity disorder, orphans, or had reading difficulties, or in correctional schools/institutions. The quality of the 13 studies ranged from low to high based on the PEDro (Physiotherapy Evidence Database) scale with the average score of 6.62 out of the highest possible score of 11 (the higher the score, the higher the quality). Five of the 13 studies found a statistically significant intervention effect for at least one outcome measure of attention or executive function with medium to large effect sizes (0.3–32.03). Mindfulness-based interventions are a promising approach to targeting attention and executive function in children and adolescence, especially with the use of computerized measures as outcome measures. All identified studies included interventions with multiple treatment components, so the effects attributable to mindfulness-based training still remain undetermined. Further quality trials are needed to assess the effectiveness of mindfulness-based interventions in enhancing attention and executive function in children and adolescents.